Features of mitochondrial membrane potential of immunocompetent blood cells in children with chronic nonspecific lung diseases accompanied by pneumofibrosis - G. P. Evseeva; E. V. Knizhnikova; E. N. Suprun; S. V. Suprun; N. I. Kuderova; S. V. Pichugina; V. V. Polubentseva; T. S. Evdokimova; O. A. Lebedko (Медицинская иммунология, 2022)
Pneumofibrosis is a pathological outcome of pulmonary tissue inflammation. It can complicate any lung and bronchial disorder. The mitochondrial membrane potential reflects functional state of immunocompetent blood cells that influence progression of a chronic inflammatory process. The aim of this work was to study the features of mitochondrial membrane potential (MMP) of immunocompetent blood cells in children with chronic nonspecific lung diseases (CNPD), accompanied by pneumofibrosis. We have examined 79 children with CNPD manifesting with symptoms of focal pneumofibrosis. The group of patients included children with congenital lung malformations (43%), consequences of bronchopulmonary dysplasia (41%), chronic bronchitis (10%), post-pneumonic pulmonary fibrosis (6%). The average age of children was 6.5±1.2 years, including 43 boys (54%) and 36 girls (46%). The comparison group included 46 children with COPD without signs of pulmonary fibrosis, the control group consisted of 30 apparently healthy children. The contents of cells with reduced MMP among lymphocytes, monocytes, and granulocytes in peripheral blood was determined with JC-1 dye, using the BD FACSCalibur instrument and Cell Quest Pro software (Becton Dickinson, USA). The proportion of lymphocytes with reduced MMP in patients with COPD was similar in the children of the main and comparison group, exceeding the indexes of the control group by 1.7 times (p < 0.001). Decreased MMP of granulocytes in children with pneumofibrosis was detected 1.9 times more often than in children with fibrosis-free CNPD cases (p < 0.05), and 3.4 times more common than in children from the control group (p < 0.001). Monocytes with reduced MMM in children with pulmonary fibrosis were detected 2 times more often than in children with COPD without fibrosis (p < 0.05), and 7.3 times more frequent than in the control group (p < 0.001). The changes were more expressed in children during exacerbation of the disease. The revealed features suggest a decreased level of metabolic activity of blood cells, thus, probably, presenting an immunopathogenetic basis for development of pneumofibrosis.